2023
DOI: 10.1186/s13007-023-01043-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved estimation of aboveground biomass of regional coniferous forests integrating UAV-LiDAR strip data, Sentinel-1 and Sentinel-2 imageries

Abstract: Background Forest aboveground biomass (AGB) is not only the basis for estimating forest carbon storage, but also an important parameter for evaluating forest carbon cycle contribution and forest ecological function. Data saturation and fewer field plots limit the accuracy of AGB estimation. In response to these questions, we constructed a point-line-polygon framework for regional coniferous forests AGB mapping using field survey data, UAV-LiDAR strip data, Sentinel-1 and Sentinel-2 imageries in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In this study, the Pearson correlation coefficient is used. Many researchers have studied the correlation between vegetation indices and biomass and carbon stock [8,12,14]. Regression analysis assessed the relationship between biomass and carbon stock and vegetation indices (VIs).…”
Section: Spatial Modeling Of Cork Oak Biomass and Carbon Stockmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Pearson correlation coefficient is used. Many researchers have studied the correlation between vegetation indices and biomass and carbon stock [8,12,14]. Regression analysis assessed the relationship between biomass and carbon stock and vegetation indices (VIs).…”
Section: Spatial Modeling Of Cork Oak Biomass and Carbon Stockmentioning
confidence: 99%
“…Satellite imagery allows large scale biomass and carbon stock analysis, but does not provide sufficient information on stand structure as it does not penetrate the canopy, unlike LiDAR (Light Detection And Ranging). This technology provides high quality information on forest stands, but over a limited area [7,[10][11][12][13][14]. It has revolutionized biomass estimation from satellites [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Laurin et al [32] fused LiDAR data and hyperspectral data to estimate tropical forest AGB, and the results showed that the synergistic use of active and passive remote sensing data estimation could improve the estimation accuracy of the forest AGB; the results of Rana et al [33] also showed that the forest AGB estimation results were significantly improved after the UAV-LiDAR data combined with the optical remote sensing data. Wang et al [34] constructed a point-line-polygon framework for regional coniferous forest AGB mapping using field survey data, UAV-LiDAR strip data, and Sentinel-1 and Sentinel-2 imagery and analyzed the potential of multiscale wavelet transform texture and tree species stratification on the accuracy of coniferous forest AGB estimation in North China, and the highest accuracy of AGB estimation was found for creosote bush, with an R 2 of 0.78; Jiang et al [35] used Sentinel-2 images provided by GEE as a medium for continuous AGB mapping with ICESat-2, and the results showed that the estimation error of each model was significantly reduced by adding the LiDAR variable of ICESat-2 to the AGB compared with using Sentinel-2 alone. Therefore, the combination of optical remote sensing data, which characterizes the spectral features of forests, and LiDAR data, which reflects the structure of forest stands, is a new way to estimate the AGB of Moso bamboo forests.…”
Section: Introductionmentioning
confidence: 99%